Rapid detection of porcine circovirus type 4 via multienzyme isothermal rapid amplification - Li, Yuqing; Zhao, Yanli; Li, Chen; Yang, Kankan; Li, Zhe; Shang, Wenbin; Song, Xiangjun; Shao, Ying; Qi, Kezong; Tu, Jian (Frontiers in Veterinary Science, 2022)
Porcine circovirus type 4 (PCV4) is a newly emerging pathogen that was first detected in 2019 and is associated with diverse clinical signs, including respiratory and gastrointestinal distress, dermatitis and various systemic inflammations. It was necessary to develop a sensitive and specific diagnostic method to detect PCV4 in clinical samples, so in this study, a multienzyme isothermal rapid amplification (MIRA) assay was developed for the rapid detection of PCV4 and evaluated for sensitivity, specificity and applicability. It was used to detect the conserved Cap gene of PCV4, operated at 41°C and completed in 20 min. With the screening of MIRA primer-probe combination, it could detect as low as 101 copies of PCV4 DNA per reaction and was highly specific, with no cross-reaction with other pathogens. Further assessment with clinical samples showed that the developed MIRA assay had good correlation with real-time polymerase chain reaction assay for the detection of PCV4. The developed MIRA assay will be a valuable tool for the detection of the novel PCV4 in clinical samples due to its high sensitivity and specificity, simplicity of operation and short testing time.